2020
DOI: 10.1038/s41598-020-76765-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergent initiation of dialysis is related to an increase in both mortality and medical costs

Abstract: The number of patients with end-stage renal disease (ESRD) has been increasing, with dialysis treatment being a serious economic problem. To date, no report in Japan considered medical costs spent at the initiation of dialysis treatment, although some reports in other countries described high medical costs in the first year. This study focused on patient status at the time of initiation of dialysis and examined how it affects prognosis and the medical costs. As a result, all patients dying within 4 months expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As we previously reported 17 , emergent initiation of dialysis is related to increased mortality 18 20 . Patients who undergo urgent initiation of dialysis often require rapid care and the poor general condition at that time of dialysis worsens the survival rate.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…As we previously reported 17 , emergent initiation of dialysis is related to increased mortality 18 20 . Patients who undergo urgent initiation of dialysis often require rapid care and the poor general condition at that time of dialysis worsens the survival rate.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, the relationship between specialized management of patients with ESRD, emergent initiation of dialysis, and survival rate were confirmed. As we previously reported 17 , emergent initiation of dialysis is related to increased mortality [18][19][20] . Patients who undergo urgent initiation of dialysis often require rapid care and the poor general condition at that time of dialysis worsens the survival rate.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Patients with CKD need to be managed so that they can be transferred to dialysis in the best possible condition. However, dialysis is often initiated on an emergency basis [ 20 ]. Furthermore, a large epidemiological study in France reported that EDS has an independent impact on mortality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Independent variables were analyzed using two models. In Model 1, we entered items of clinical significance from among variables that showed significant differences ( p < 0.001) between the two groups, referring to previous studies [ 1 , 19 , 20 , 21 ]. In doing so, items that could be intermediate variables for causality (length of hospitalization, FIM-walking score at hospitalization, number of rehabilitations) were excluded.…”
Section: Methodsmentioning
confidence: 99%